2016
DOI: 10.1136/archdischild-2016-311034
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for arterial ischaemic stroke in childhood: a systematic review

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Two papers that addressed the use of steroids in childhood AIS were identified. 74,75 A systematic review of 32 observational studies and two trials involving 152 children provided weak evidence for the benefits of steroid treatment in childhood AIS, in the context of tuberculous or bacterial meningitis, and some subtypes of arteriopathy. It was noted, however, that the studies reviewed had no internal controls or comparison groups.…”
Section: Section 4: Recommendations For Primary Pediatric Stroke Centmentioning
confidence: 99%
“…Two papers that addressed the use of steroids in childhood AIS were identified. 74,75 A systematic review of 32 observational studies and two trials involving 152 children provided weak evidence for the benefits of steroid treatment in childhood AIS, in the context of tuberculous or bacterial meningitis, and some subtypes of arteriopathy. It was noted, however, that the studies reviewed had no internal controls or comparison groups.…”
Section: Section 4: Recommendations For Primary Pediatric Stroke Centmentioning
confidence: 99%
“…The authors concluded that there was little robust evidence in favor or against the use of immunotherapy in childhood AIS. 32 Another study of 27 children found no reduction in rates of vascular progression in children receiving steroids. 34 A retrospective Australian and Swiss study compared outcomes between 21 children with AIS due to an FCA treated with combined corticosteroid and antithrombotic treatment, and 53 treated with antithrombotic treatment alone.…”
Section: Arteriopathies In Pediatric Stroke Predictive Biomarkers Amentioning
confidence: 98%
“…31 Three studies have assessed the use of corticosteroids in pediatric stroke. [32][33][34] A systematic review of studies involving 152 children with stroke provided very weak evidence for the benefits of steroid treatment in the context of tuberculous or bacterial meningitis, and some subtypes of arteriopathy. The studies reviewed had no internal controls or comparison groups.…”
Section: Treatmentsmentioning
confidence: 99%
“…Although anecdotally corticosteroids have been used in post-varicella arteriopathy, and focal cerebral arteriopathy of childhood, a recent systematic review of 34 studies concluded that robust evidence of efficacy is lacking. 61 A recent physician survey concluded that a clinical trial of corticosteroids in focal cerebral arteriopathy of childhood is a priority (with concomitant use of acyclovir in post-varicella arteriopathy). 62 However, a recent analysis of 84 UK AIS cases did not find a high recurrence rate in focal cerebral arteriopathy of childhood.…”
Section: Treatmentmentioning
confidence: 99%